Breaking dawn - Meyer, Stephenie, 1973- (New York : Megan Tingley Books/Little, Brown and Co.; Atom, 2008)
Although eighteen-year-old Bella joins the dark but seductive world of the immortals by marrying Edward the vampire, her connection to the powerful werewolf Jacob remains unsevered.
Originally published: New York : Little, Brown, 2008.
Keywords: Vampires -- Fiction; Werewolves -- Fiction; Paranormal fiction; Marriage -- Fiction; Triangles (Interpersonal relations) -- Fiction; Washington (State) -- Fiction; Fantasy fiction; Young adult fiction